Current Status of Ceratobasidium theobromae Affecting Cacao and Cassava: Diagnosis and Management - Cansu Oksel; Fulya Baysal-Gurel (Plant Health Progress, 2026)
Ceratobasidium theobromae, the causal agent of vascular streak dieback in cacao, has recently been associated with cassava witches’ broom disease, expanding its known host range and increasing its importance in crop production systems. This review summarizes disease development, diagnosis, and management of C. theobromae in cacao and cassava. Diagnosis remains challenging due to difficulties in pathogen isolation and confirmation of pathogenicity, although molecular tools have improved detection and identification. Management relies mainly on preventive measures, including sanitation, healthy planting material, host tolerance, and phytosanitary practices, as effective curative options are limited. Improved diagnostics, surveillance, and management practices will be important for reducing the impact of this pathogen in cacao and cassava production systems.